Enterovirus A Shows Unique Patterns of Codon Usage Bias in Conventional Versus Unconventional Clade - Zeng, Liyan; Chen, Ming; Wang, Min; Zhu, Liuyao; Yan, Jingjing; Zhang, Xiaoyan; Xu, Jianqing; Zhang, Shuye (Frontiers in Cellular and Infection Microbiology, 2022)
Enterovirus A (EV-A) species cause hand, foot and mouth disease (HFMD), threatening the health of young children. Understanding the mutual codon usage pattern of the virus and its host(s) have fundamental and applied values. Here, we found that the codon usage bias among EV-A strains varies and is clade-specific. EVA76, EVA89, EVA90 and EVA91, and EVA92, the unconventional clade of EV-A strains, show unique codon usage pattern versus the two conventional clades. Codon usage patterns of EV-A strains are shaped by mutation pressure and natural selection. Based on the neutrality analysis, we determined the dominant role of natural selection in the formation of the codon usage bias of EV-A. In addition, we have determined the codon usage compatibility of potential hosts for EV-A strains using CAI, RCDI and SiD analysis, and found that EV-A showed host-specific codon adaptation patterns in different clades. Finally, we confirmed that the unique codon usage pattern of the unconventional clade affected protein expression level in human cell lines. In conclusion, we identified novel characteristics of codon usage bias in distinct EV-A clades associated with their host range, transmission and pathogenicity.